PENGEMBANGAN PEMAHAMAN PEMBELAJARAN BACA TULIS AL-QUR’AN PADA ANAK-ANAK DI WILAYAH NAGARI RIAK DANAU TAPAN - Wisda, Rini Syevyilni; Padrian, Rahmad Pani; Pohan, Muhammad Munawir; Erniyati, Yelni (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service is carried out with the aim of increasing children's love of learning by learning to read and write the Al-Qur'an in a fun way for the children of Nagari Riak Danau Tapan. The low interest in learning to write and read the Al-Qur'an that occurs in the current generation has motivated researchers to devote themselves to cultivating enthusiasm through developing science with the younger siblings of Riak Danau Tapan. This service effort aims to reduce and overcome the problems that occur among generations who have been far from religious education, the Al-Qur'an and religious sciences. The steps taken in this service are firstly observing how the children are in terms of background achievements, children's motivation and so on. This activity aims to analyze and provide and find appropriate solutions for the process of developing understanding of Al-Qur'an knowledge. Second, invite children to learn to write and read the Al-Qur'an using the method of learning while playing through tutoring or fun study guidance, third, carrying out activities to return to the surau, inviting children to take part in activities facilitated by Nagari by holding the Al-Qur'an in mosques. or MDA.